Defects interaction processes in deformed high purity polycrystalline molybdenum at elevated temperatures - Lambri, Osvaldo Agustin F. (2014)
Mechanical spectroscopy (damping and elastic modulus as a function of temperature) and transmission electron microscopy studies have been performed in high purity polycrystalline molybdenum plastically deformed to different values of tensile and torsion strain. Mechanical spectroscopy measurements were performed from room temperature up to 1285 K. A relaxation peak in polycrystalline molybdenum related to the movement of dislocations into lower energy configurations near grain boundaries has been discovered to appear around 1170 K. The activation energy of the peak is 4.2 eV ± 0.5 eV. This relaxation phenomenon involves the interaction between vacancies and mobile dislocations near the grain boundaries. It should be highlighted that this relaxation process is controlled by the arrangement of vacancies and dislocations which occur at temperature below 1070 K